Multimedia fushion dalam perisian penceritaan interaktif visual bagi aplikasi sains peringkat prasekolah - Robiatul A'Dawiah Jamaluddin; Halimah Badioze Zaman (Universiti Malaysia Kelantan, 2015)
Multi-media applications or multimedia fusion, refers to the integration of more than one media such as text, graphic, animation, audio and video in multi digital environments such as virtual reality, augmented reality and mixed reality. These applications have potential to be effective teaching and learning aids that can enhance understanding and achievement of preschool learners, epecially on topics that are abstract and complex in nature. Results of the statistical analysis on the post test for the Controlled (K) and Experimental (E) groups, showed that there was a significant difference in the learning of the topic on Solar System with the theme Exploring Outerspace by the Experimental group (E) when compared to the Controlled group (K) [t(df=40)=2.895, p=0.008]. The mean indicated for the post test results by the Controlled group (K) was 9.571; and the mean indicated for the post test results by the Experimental group (E) was 11.381. Thus, these findings showed that the achievement of preschool learners from the Experimental group (E) was higher as compared to learners from the Controlled group (K).